Mesenchymal Stem Cell-Immune Cell Interaction and Related Modulations for Bone Tissue Engineering - Renxin Chen; Zhuowen Hao; Yi Wang; Hongzhen Zhu; Yingkun Hu; Tianhong Chen; Peng Zhang; Jingfeng Li (Hindawi Limited, 2022)
Critical bone defects and related delayed union and nonunion are still worldwide problems to be solved. Bone tissue engineering is mainly aimed at achieving satisfactory bone reconstruction. Mesenchymal stem cells (MSCs) are a kind of pluripotent stem cells that can differentiate into bone cells and can be used as one of the key pillars of bone tissue engineering. In recent decades, immune responses play an important role in bone regeneration. Innate immune responses provide a suitable inflammatory microenvironment for bone regeneration and initiate bone regeneration in the early stage of fracture repair. Adaptive immune responses maintain bone regeneration and bone remodeling. MSCs and immune cells regulate each other. All kinds of immune cells and secreted cytokines can regulate the migration, proliferation, and osteogenic differentiation of MSCs, which have a strong immunomodulatory ability to these immune cells. This review mainly introduces the interaction between MSCs and immune cells on bone regeneration and its potential mechanism, and discusses the practical application in bone tissue engineering by modulating this kind of cell-to-cell crosstalk. Thus, an in-depth understanding of these principles of bone immunology can provide a new way for bone tissue engineering.